Recent Research on the Andes before Independence: Ethnohistory, Social History, and Revolt and Revolution - Ramírez, Susan E. (History compass, 2009)
Over the last few decades, scholars of the Andes have peopled the institutions studied and defined by previous generations of investigators. The resulting scholarship shows the sometimes stark contrast between legal theory and practice through the re-telling of incidents and anecdotes and the analysis of the collective biographies of Spanish colonists, native peasants, blacks, and mixed-bloods (the castas). This overview will highlight the contributions of recent research on native societies, social history, and the mounting instability that characterized the eighteenth century.